2011
DOI: 10.1172/jci46279
|View full text |Cite
|
Sign up to set email alerts
|

Signaling via the prostaglandin E2 receptor EP4 exerts neuronal and vascular protection in a mouse model of cerebral ischemia

Abstract: Stroke is the third leading cause of death in the United States. Fewer than 5% of patients benefit from the only intervention approved to treat stroke. Thus, there is an enormous need to identify new therapeutic targets. The role of inducible cyclooxygenase (COX-2) activity in stroke and other neurologic diseases is complex, as both activation and sustained inhibition can engender cerebral injury. Whether COX-2 induces cerebroprotective or injurious effects is probably dependent on which downstream prostagland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 54 publications
6
93
0
Order By: Relevance
“…Moreover, they observed that cognitive function of mice in an Alzheimer's disease model was improved by genetic and pharmacological inhibition of EP4 (Hoshino et al, 2012). In contrast, Liang et al (2011) reported that an EP4 receptor agonist exerted a protective effect against cerebral ischemia injury in mice. Deletion of neuronal EP4 increased the severity of cerebral injury, as did endothelial deletion of EP4.…”
Section: +mentioning
confidence: 99%
“…Moreover, they observed that cognitive function of mice in an Alzheimer's disease model was improved by genetic and pharmacological inhibition of EP4 (Hoshino et al, 2012). In contrast, Liang et al (2011) reported that an EP4 receptor agonist exerted a protective effect against cerebral ischemia injury in mice. Deletion of neuronal EP4 increased the severity of cerebral injury, as did endothelial deletion of EP4.…”
Section: +mentioning
confidence: 99%
“…Recently an exciting approach to studying the effect of prostaglandins in the brain was described in a stroke model (31). The COX-2 product prostaglandin E2 can bind to four different prostanoid receptors making it difficult to understand how COX-2 inhibitors, which seem to strongly reduce risk of AD (32) and PD (33), work in the brain.…”
Section: Immune Responses By Neuronsmentioning
confidence: 99%
“…The COX-2 product prostaglandin E2 can bind to four different prostanoid receptors making it difficult to understand how COX-2 inhibitors, which seem to strongly reduce risk of AD (32) and PD (33), work in the brain. Liang and coworkers showed that genetic deletion of prostanoid receptor 4 in neurons worsened stroke injury and decreased cerebral perfusion, pointing to a beneficial effect of this receptor in neurons (31). Clearly, this is a direction in which the field of neurodegeneration has to move in order to gain a more complete understanding of the complex action of immune factors in neuronal distress and degeneration.…”
Section: Immune Responses By Neuronsmentioning
confidence: 99%
“…Our findings are consistent with a robust expression of EP 4 in neurons and in endothelial cells after cerebral ischemia, suggesting a protective sensory cellular mechanism. 61 Along these lines, PGE 2 and EP 4 agonists have recently been patented as a method to treat ischemic episodes (US 2010/0267826 A1).…”
Section: Inset) No Increase In Expression Is Observed In Gpr91mentioning
confidence: 99%